Pengaruh Motivasi, Kompetensi Dan Reformasi Birokrasi Terhadap Kinerja Pegawai - Nunung Nurjanah (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
This research is motivated by problems with the performance of the Education and Culture Office employees who are still not optimal. Many factors influence this performance, three of which are Motivation, Competence and Bureaucratic Reform. Thus, the purpose of this study is to find out and describe the influence of motivation, competence and bureaucratic reform on the performance of employees of the Banjar City Education and Culture Office. The method used is descriptive qualitative with the results of the study showing that work motivation tends to be very high, as well as very high employee performance. Thus, motivation influences employee performance. This means that if motivation increases, it will be followed by an increase in the performance of the Banjar City Education and Culture Office employees. Competence tends to be very high, as well as very high employee performance. Thus, competence affects employee performance. This means that if competence increases, it will be followed by an increase in the performance of the Banjar City Education and Culture Office employees. Bureaucratic reform tends to be very high, as well as very high employee performance. Thus, if bureaucratic reform affects employee performance. This means that if bureaucratic reform increases, it will be followed by an increase in the performance of the Banjar City Education and Culture Office employees. Motivation, competence and work bureaucratic reform tend to be very high, as well as very high employee performance. Thus, motivation, competence and bureaucratic reform affect employee performance. This means that if motivation, competence and bureaucratic reform increase, it will be followed by an increase in the performance of the Banjar City Education and Culture Office employees